A Thematic Analysis On Group Communication : How do University students evaluate themselves and what role does English as a lingua franca play? - Charalampous, Eleni (2024)
In higher education institutions students very often have to collaborate in groups in order to complete a task. This study examines how international students of a mid-size university in Finland, experience group communication and how they evaluate them-selves in terms of their contribution and participation considering that they use English as a lingua franca. Interview data from individual and group interviews (n=18) were analyzed using qualitative thematic analysis. The findings illustrate how various as-pects such as diversity, culture, social and personal background, previous group experiences and English language skills become relevant through participants’ group experiences. In general, this thesis contributes to identify the feelings students have during collaborative working, by highlighting the benefits and obstacles they face. Results also show how the idea of self-concept is affecting students’ academic performance and communication in the group. The theoretical and societal implications of studying groups in higher education institutions are discussed, taking into account that students’ perspectives could be further examined in research. By increasing understanding on the role of English as a language of instruction, diversity and sociocultural background, academics will be able to offer students better group work experiences in various levels.